2001
DOI: 10.1097/00000421-200104000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Local Control and Survival After Concomitant Boost Accelerated Radiotherapy for Locally Advanced Cervix Cancer

Abstract: Between 1989 and 1994, a prospective clinical trial tested the safety and efficacy of concomitant boost accelerated superfractionated (CBASF) radiotherapy for patients with locally advanced cervix cancer. CBASF radiotherapy included 45 Gy/25 fractions to the pelvis and a 14.4 Gy/9 fraction concomitant boost to the primary tumor, followed by brachytherapy for a total point A dose of 85 Gy to 90 Gy. The 22 patients of International Federation of Gynecology and Obstetrics stages IIIA-IVA who received CBASF radiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The rationale for AHF is that overall treatment time is shortened thereby decreasing the accelerated repopulation and AHF may result in better local control. Today, some reports of radiotherapy results with AHF for cervical cancer have been published [24,25]. Kavanagh et al treated cervical cancer with concomitant boost accelerated superfractionated (CBASF) radiotherapy followed by ICBT and they concluded that CBASF radiotherapy produced a trend toward improved local control when compared with conventional fractionated radiotherapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for AHF is that overall treatment time is shortened thereby decreasing the accelerated repopulation and AHF may result in better local control. Today, some reports of radiotherapy results with AHF for cervical cancer have been published [24,25]. Kavanagh et al treated cervical cancer with concomitant boost accelerated superfractionated (CBASF) radiotherapy followed by ICBT and they concluded that CBASF radiotherapy produced a trend toward improved local control when compared with conventional fractionated radiotherapy [25].…”
Section: Discussionmentioning
confidence: 99%